Expanded algal cultivation can reverse key planetary boundary transgressions. Issue 2 (February 2018) - Calahan, Dean; Osenbaugh, Edward; Adey, Walter
Abstract: Humanity is degrading multiple ecosystem services, potentially irreversibly. Two of the most important human impacts are excess agricultural nutrient loading in our fresh and estuarine waters and excess carbon dioxide in our oceans and atmosphere. Large-scale global intervention is required to slow, halt, and eventually reverse these stresses. Cultivating attached polyculture algae within controlled open-field photobioreactors is a practical technique for exploiting the ubiquity and high primary productivity of algae to capture and recycle the pollutants driving humanity into unsafe regimes of biogeochemical cycling, ocean acidification, and global warming. Expanded globally and appropriately distributed, algal cultivation is capable of removing excess nutrients from global environments, while additionally sequestering appreciable excess carbon. While obviously a major capital and operational investment, such a project is comparable in magnitude to the construction and maintenance of the global road transportation network. Beyond direct amelioration of critical threats, expanded algal cultivation would produce a major new commodity flow of biomass, potentially useful either as a valuable organic commodity itself, or used to reduce the scale of the problem by improving soils, slowing or reversing the loss of arable land. A 100 year project to expand algal cultivation to completely recycle excess global agricultural N and P would, when fully operational, require gross global expenses no greater than 2.3 × 10 12 yr −1, (3.0% of the 2016 global domestic product) and less than 1.9 × 10 7 ha (4.7 × 10 7 ac), 0.38% of the land area used globally to grow food. The biomass generated embodies renewable energy equivalent to 2.8% of global primary energy production.